Endothelial dysfunction prognostic role in cardiovascular pathology - T. S. Romanenko; M. G. Omelyanenko; A. V. Kontsevaya (Кардиоваскулярная терапия и профилактика, 2008)
Endothelial dysfunction (ED) amplifies the effects of vascular risk factors (RF), and is directly linked to pathogenetic mechanisms of atherosclerosis and its complications. To clarify ED prognostic role, a review of relevant studies was performed. ED interrelation with various clinical outcomes of cardiovascular disease (CVD) was demonstrated. At the moment, the main method of 5-10-year CVD risk assessment in CVD patients and asymptomatic individuals is evaluation of total mortality risk. ED could be an independent marker of atherosclerosis, including its subclinica course, and a predictor of various CVD events. Endothelium may link various RF and their damaging effect on vascular wall. Future studies will confirm whether endothelial function assessment could be used for dynamic follow-up of CVD patients, as a measure of prevention effectiveness.